PENGEMBANGAN DESA SILANGJANA SEBAGAI DESA WISATA BERBASIS EKOWISATA - Hendrayana, Kadek Agus; Dianasari, Dewa Ayu Made Lily; Negarayana, Ida Bagus Putra (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
Silangjana Village is one of the tourist villages in Bali, Silangjana village is part of the pioneer tourism village. When viewed from the Tourism Area Life Cycle, Silangjana Village is in the exploration where the tourist attractions owned are partly based on nature. The attractions are mostly natural and cultural themes that have yet to be thoughtfully developed. This study aims to identify ecotourism products that can be developed in Silangjana Village. This study uses qualitative descriptive analysis techniques and data collection using interview and observation methods. The result is that ecotourism products that can be developed consist of attractions and activities based on ecotourism. The Silangjana Village ecotourism products are Candi Kuning Waterfall, Dukuh Pajenengan Temple, Pucak Padi Mas Temple, campsites, and palm sugar. In addition, there is potential for ecotourism activities such as tubing, cycling, trekking, and climbing activities.